Neighbours and successors of Rome : traditions of glass production and use in Europe and the Middle East in the later 1st millennium AD - Keller, Daniel, 1970-; Price, J. (A. Jennifer); Jackson, Caroline M. (Oxbow Books, 2014)
"Neighbours and Successors of Rome investigates development in the production of glass and the mechanisms of the wider glass economy as part of a wider material culture in Europe and the Near East around the later first millennium AD. Though highlighting and solidifying chronology, patterns of distribution, and typology, the primary aims of the collection are to present a new methodology that emphasises regional workshops, scientific data, and the wider trade culture"--